HER2 expression and pathway status in male breast cancer patients: results of an integrated analysis among 6,150 patients - Boqiang Lyu; Shidi Zhao; Hui Wang; Shouping Gong; Biyuan Wang (Scientific Reports)
Abstract The role of human epidermal growth factor 2 (HER2) in male breast cancer (MBC) is poorly defined. A comprehensive description of HER2 status was conducted. A total of 6,015 MBC patients from 45 studies and 135 MBC patients with sequencing data were identified. HER2 positive rates and hazard ratios (HR) for overall survival (OS) were combined using Metaprop. The prevalence of HER2 + MBC was 10.0% (95% CI: 8.0-13.0%). Subgroup analyses showed that 7% (95% CI: 2.0-14.0%) had HER2 + protein overexpression. 10% of MBC patients had HER2 + overexpression and/or gene amplification. Asian MBC patients had the highest HER2 + incidence of 17% (95% CI: 12.0-22.0%). The prevalence of HER2 positive MBC fluctuated widely from 2001 to 2015 and then stabilized at 10%. HER2 positivity was significantly correlated with worse OS than negative ones (HR = 1.92, 1.47–2.51). The proportion of HER2 + MBC was inconsistent with the results for the intrinsic HER2-enriched subtype. Altered genes in HER2 + MBC, such as ERBB2, AGO2, RECQL4, and CLTC, were not detected in HER2-MBC. Genomic analysis revealed differences between the patients with HER2 + MBC and those with HER2 + FBC. The percentage of HER2 + MBC was slightly lower than that of women. Multiple approaches may be needed to jointly assess HER2 status in MBC.